Adipocyte-derived IL6 and triple-negative breast cancer cell-derived CXCL1 co-activate STAT3/NF-κB pathway to mediate the crosstalk between adipocytes and triple-negative breast cancer cells - Guo-Tian Ruan; Li-Chen Zhu; Hai-Lun Xie; He-Yang Zhang; Meng-Meng Song; Li Deng; Han-Ping Shi (Cell Death Discovery)
Abstract Triple-negative breast cancer (TNBC) is correlated to a poor prognosis, especially in the context of obesity. The interaction between adipocytes and TNBC cellsplay a key role in the progression of TNBC. This study aims to investigate the mechanisms underlying the cross-talk and progression between adipocytes and TNBC cells. We established a co-culture model involving mature adipose cells (hADSC and 3T3-L1) and TNBC cells. Cell invasion abilities were assessed using wound healing and Transwell assays. Gene and protein expression levels were examined using RT-PCR, western blotting, and immunostaining. Adipocytokine and chemokine levels were measured using ELISA. Additionally, we developed a fat mouse model induced by a high-fat diet and a tumor-bearing model of TNBC cells in vivo. The results indicated a significant enhancement in the invasion abilities of TNBC cells after co-culture. Mature adipose tissue co-cultured with TNBC cells increased the expression and secretion of C-X-C motif chemokine ligand 1 (CXCL1) and upregulated matrix metalloproteinase 7 (MMP7) and MMP9 in TNBC cells by activating the signal transducer and activator of transcription 3 (STAT3) /nuclear factor-κB p65 (NF-κB p65) pathway. Additionally, co-culture activated the STAT3/NF-κB p65 pathway, increasing the expression and secretion of IL6 in adipocytes. Based on the mouse obesity model, our experiments on orthotopic breast fat pad xenoimplantation showed consistent results in vivo. Our findings suggest a cross-talk between TNBC cells and adipocytes, activating the STAT/NF-κB p65 pathway through the production and secretion of CXCL1 and IL6, respectively, thereby promoting TNBC progression. These results propose a potential strategy for developing individualized treatments for patients with TNBC in clinical practice.